Does Increasing the Bend Angle of a Stylet to 90° Increase the Nasotracheal Intubation Success Rate? - Liu, Juhui; Xu, Wenli; Jin, Zibin; Deng, Xiaoming (Journal of oral and maxillofacial surgery, 2024)
Video-stylet-guided nasotracheal intubation (NTI) is an effective technique for airway management. However, the impact of the bend angle on the success rate of intubation remains unclear. Does increasing the bend angle of a stylet to 90° increase NTI success rate?. This prospective randomized controlled trial was conducted in the operating room of a population-based hospital. Adult patients requiring NTI were recruited. The primary predictor variable is the choice of stylet bend angle (90° vs 70° bend) in NTI. The primary outcome variables were success rates of NTI, defined as the proportion of successful intubation cases to total cases. Demographics, intubation time, the distance from the thyroid prominence to the nostril, additional maneuvers applied during intubation, and cases of epistaxis were recorded. The student's t-test was used to compare continuous variables between groups. Ordinal data (intubation attempts, head extension, and epistaxis) were analyzed using the Wilcoxon rank-sum test. As appropriate, frequency (external pharyngeal pressure) was analyzed using the χ2 test or Fisher's exact test. A P value of <.05 was considered statistically significant. Of the 103 subjects assessed for eligibility, 98 were enrolled in the study. The mean age (27.0 ± 6.9 years vs 27.0 ± 4.1 years, P = .972) and sex differences (male/female: 9/40 vs 7/42, P = .136) were comparable between groups. The overall success rate in the 70° group was significantly lower than that in the 90° group (91.8 vs 100%, P < .001). The intubation time in the 70° group was significantly longer than that in the 90° group (43.2 ± 15.8 s vs 33.7 ± 7.3 s, P < .001). A 90° bend angle of the stylet significantly improves the likelihood of successful NTI.